2014
DOI: 10.5713/ajas.2014.14139
|View full text |Cite
|
Sign up to set email alerts
|

Testicular Cell Indices and Peripheral Blood Testosterone Concentrations in Relation to Age and Semen Quality in Crossbred (Holstein Friesian×Tharparkar) Bulls

Abstract: Present study analyzed the changes in peripheral blood testosterone concentrations and testicular cytogram in relation to age and semen quality in crossbred males. Three different age groups of crossbred males viz. bull calves (6 months, n = 5), young bulls (15 months, n = 5) and adult bulls (4 to 6 years, n = 8) were utilized for the study. Testicular fine needle aspiration cytology technique was used to quantify testicular cytology and their indices. Peripheral blood testosterone concentrations were measured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 36 publications
(41 reference statements)
2
15
0
Order By: Relevance
“…On the other hand, sperm traits can evolve independently but in the same direction (reviewed by [ 61 ]), because they share the same goal and are the final product of an efficient spermatogenesis. In spite of some discrepancies in what sperm number and quality parameters are considered, our findings are consistent with inter- [ 14 , 62 , 63 ] and intra-specific [ 9 , 22 , 64 ] studies supporting that sperm quantity and quality are correlated with one another most likely to maximise sperm fertilisation efficiency in red deer.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…On the other hand, sperm traits can evolve independently but in the same direction (reviewed by [ 61 ]), because they share the same goal and are the final product of an efficient spermatogenesis. In spite of some discrepancies in what sperm number and quality parameters are considered, our findings are consistent with inter- [ 14 , 62 , 63 ] and intra-specific [ 9 , 22 , 64 ] studies supporting that sperm quantity and quality are correlated with one another most likely to maximise sperm fertilisation efficiency in red deer.…”
Section: Discussionsupporting
confidence: 88%
“…Our findings also reveal that the Sertoli cell number is positively associated with sperm parameters in red deer, supporting what was recently found by Rajak et al . [ 9 ] in bull. Therefore, changes in the Sertoli cell number not only affect the magnitude of sperm production [ 43 ], but also sperm function.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While the relative importance of either hormone appears somewhat different between rodents and primates, generally, however, both LH/testosterone and FSH are necessary for quantitatively normal spermatogenesis, at least in non-seasonal species. Borg et al (1991) found no significant alterationsin testosterone levels associated with sexual behavior, although values were different for Angus bulls with different reproductive behavior performanceand different age (Sekoni et al, 2010;Rajak et al, 2014). As a result of increase concentrations of LH hormone leads to decrease testosterone hormone concentration in group IV that could ultimately lead to low libido behavior of group II and III (Table 2).…”
Section: Profile Of Testosterone and Lh Hrmonesmentioning
confidence: 98%